a, x+7x-19x-6x b, -ab-ab c, -12(x-5)+7(3-x) d, 30(x+2)-6(x-5)-24x

a, x+7x-19x-6x

b, -ab-ab

c, -12(x-5)+7(3-x)

d, 30(x+2)-6(x-5)-24x

2 bình luận về “a, x+7x-19x-6x b, -ab-ab c, -12(x-5)+7(3-x) d, 30(x+2)-6(x-5)-24x”

  1. Giải đáp:
     
    Lời giải và giải thích chi tiết:
     x+7x-19x-6x
    =(x+7x)-(19x-6x)
    =8x-25x
    =-17x
    -ab-ab
    =ab+(-ab)
    =-2ab
    12(x-5)+7(3-x)
    =12x+60+21-7x
    =(-12x-7x)+(60+21)
    =(-19x)+71
    =-52
    30(x+2)-6(x-5)-24x
    =30x+60-6x+30-24x
    =(3x=6x-24x)+(60+30)
    =60+30
    =90

    Trả lời
  2. Tính:
    a) x + 7x – 19x – 6x
    = (x + 7x) – ( 19x + 6x)
    = 8x – 25x
    = -17x
    b) -ab – ab
    = -ab + (-ab)
    = -2ab
    c) -12( x – 5) + 7(3 – x)
    = -12x + 60 + 21 – 7x
    = (-12x – 7x) + (60 + 21) 
    = (-19x) + 71
    d) 30( x + 2) – 6( x- 5) – 24x
    = 30x + 60 – 6x + 30 – 24x
    = (30x – 6x – 24x) + (60 + 30)
    = 60 + 30
    = 90
     

    Trả lời

Viết một bình luận

Câu hỏi mới